Effect of honey spraying on the growth of habanero pepper seedlings - González-Rodríguez, Felipe de Jesús (2026)
Introduction. Foliar spraying with honey represents a sustainable alternative for seedling production. Objective. To evaluate the effect of foliar spraying with multifloral honey (Apis mellifera) at concentrations of 5 %, 10 %, and 15 % v/v on plant height, stem diameter, number of leaves, and nitrogen, phosphorus, and potassium concentrations in habanero pepper seedlings (Capsicum chinense L. Jacq.) under protected conditions. Materials and methods. The study was conducted in a sawtooth-type greenhouse at the Instituto Tecnológico Superior de Calkiní, Campeche, Mexico, from August to December 2023. Seeds of the ‘Jaguar’ variety were sown in eight trays containing commercial substrate. A randomized complete block design with four treatments and two replications was used, and weekly foliar spraying with honey was applied. Seedling height, stem diameter, number of leaves, and nitrogen, phosphorus, and potassium concentrations were evaluated. Analysis of variance (ANOVA) and multiple range tests using Fisher’s least significant difference (LSD) method (p < 0.05) were performed for each growth variable. Results. The 15 % honey treatment promoted greater seedling height; the control without honey showed the lowest growth and the highest variability during the evaluation weeks. Regarding stem diameter, T4 and T3 showed greater growth and consistency across the three weeks compared to the control. T2 initially favored the number of leaves; however, in later weeks, T4 reached the highest mean values. Conclusions. Foliar application of multifloral honey significantly improved the height, stem diameter, and number of leaves in habanero pepper seedlings, which showed greater growth and uniformity compared to the control, with the 15 % v/v treatment being the most effective.